‘Waar is beter dorp in Zuid Africa dan Stellenbos?’ : What the Stellenbosch-Drakenstein Tax Censuses Reveal - Fourie, Johan; Green, Erik; Burger, Christiaan; de Wit, Chris; Ekama, Kate; Greyling, Jan; Heese, Hans; Pretorius, Jan Hendrik; Ross, Robert; von Fintel, Dieter (South African Historical Journal, 2025)
In 1825, an unnamed Stellenbosch official paused his tax collection duties to pen a poem in the margins of the opgaafrol. His verses capture the frustrations of colonial administration but the records themselves–annual tax censuses spanning 1685 to 1844–offer a far richer window into the Cape Colony’s social and economic history. First established by the Dutch East India Company and later maintained under Batavian and British rule, the opgaafrollen documented household composition, agricultural production, and patterns of coerced labour. While these records have long informed scholarship, their fragmented nature has limited systematic analysis. This article introduces a newly transcribed series of opgaaf records for Stellenbosch and Drakenstein. We examine three key themes: surname frequency as a proxy for marriage patterns and kinship networks; long-term shifts in agricultural output; and changes in slave ownership. Our findings challenge existing interpretations of colonial economic mobility and governance, demonstrating how settler households navigated taxation, labour, and status. By analysing the opgaafrollen at scale, this study rethinks their role–not simply as tax records but as a tool for understanding economic and social change in the eighteenth- and nineteenth-century Cape Colony.
Keywords: Cape Colony; Dutch East India Company; quantitative history; slavery; taxation